UNDERSTANDING THE DETERMINANTS OF RESIDENT SUPPORT FOR HALAL TOURISM SUSTAINABILITY IN POST-COVID-19 (Journal of Event, Tourism and Hospitality Studies, 2025)
This conceptual article focuses on Malaysia's halal tourism sector, which is vital to the country's economic growth. One of the most significant economic sectors where sustainability has gained importance is halal tourism. Without the active support of residents, halal tourism cannot be sustained; nevertheless, while local support for other forms of tourism sustainability has been extensively researched, local support for halal tourism sustainability has received far less attention. Furthermore, it is critically necessary to look into the suppositions that can affect residents' support for sustainable halal tourism. Unfortunately, the quick spread of the COVID-19 outbreak in 2019 resulted in significant losses for the halal tourism industry, both locally and globally, due to the cancellation of majority travel and tour-related activities, including lodging. More research is needed to determine how the pandemic has affected halal tourism in terms of residents' support for halal tourism and its long-term sustainability. Thus, this conceptual study seeks to understand the residents’ attitude and behaviour as well as how residents perceive sustainable halal tourism in their destination. A structured literature review was conducted in this study, with the aim to develop a conceptual framework of residents’ support based on review of literature for sustainable halal tourism development. Importantly, this conceptual work will act as the foundation for future, more focused research in this field.